Web design playground - McFedries, Paul (Manning Publications, 2024)
Web Design Playground, Second Edition takes a creative, visual approach and clear explanations of the components, concepts, and of each step you'll need to build your own web pages. You'll become a confident web designer as you practice each new skill in the Playground. The many small projects introduce everything from page layout basics to new tags and features like Flexbox and CSS Grid-all presented in author Paul McFedries's inimitably friendly style. Don't worry about setting up your own servers and domain names-the book comes with a free online "playground" to experiment with and get creative. You can concentrate on core skills like page layout and adding images and video, as well as learning typography, responsive design, and the other modern web design techniques. Before you know it, you'll be ready to create gorgeous pages that reflect your creativity and style.
Includes index
Keywords: HTML (Document markup language); Cascading style sheets; Web site development -- Computer programs; Web sites -- Design; HTML (Langage de balisage); Feuilles de style en cascade; Sites Web; Systèmes-auteur; Sites Web; Conception; HTML